Factors influencing attitude towards technology adoption among Permanent Food Production Park (PFPP) program participants in West Malaysia - Zulqarnain; Man, Norsida; Sharifuddin, Juwaidah; Roslan, Muhammad; Hassan, Salim (David Publishing, 2020)
The study explores the factors influencing attitude towards agricultural technology adoption among Permanent Food Production Park (PFPP) program participants in West Malaysia and the factors that influence their attitudes. The PFPP program is one of the programs introduced by the government of Malaysia with the objectives of increasing food production, as well as supporting local agriculture entrepreneurs. The study employed a cross-sectional study design and has been conducted in four West Malaysian states with a sample of size of 275 respondents. The results indicated that the respondents had a positive attitude towards technology adoption and factors such as knowledge and skill, benefit, education level, years of experience in agriculture and gross income had influenced their attitude.